Developing a Mathematics Instructional Model to Enhance Computational Thinking Skills among Pre-service Mathematics Teachers in Support of the Sustainable Development Goals: A Bibliometric Analysis and Empirical Study - Nitiphoom Adsawatithisakul; Kanyarat Cojorn (ASEAN Journal of Educational Research and Technology, 2026)
Computational thinking is essential for preparing future mathematics teachers to address complex problems in digital and sustainable education. This study developed and evaluated a mathematics instructional model for pre-service mathematics teachers using a descriptive bibliometric analysis and an empirical research-and-development approach. Scopus data showed rapid growth in publications on computational thinking from 1987 to 2025, confirming its increasing educational relevance. The model comprised six stages: situation presentation, analysis, association, synthesis, designing and arranging problem-solving procedures, and conclusion. 30 participants completed a one-group pretest-posttest implementation. Results showed significant improvements in decomposition, pattern recognition, abstraction, and algorithm design, supported by positive interview responses. The model provides a framework for computational thinking development and supports SDG-oriented quality teacher education.